Методика расчета термохимического реактора конверсии метанола - Баранов, В. Ю.; Асташов, Р. Н. (НТУ "ХПИ", 2012)
В статье рассмотрена методика расчета термохимического реактора конверсии метанола: расчет параметров греющего теплоносителя (отработавших газов) и количества катализатора; определение размера реактора и коэффициента теплоотдачи в межтрубном пространстве.

This article is about the method used to calculate thermochemical conversions in methanol reactor: the calculation of the heated thermal medium (exhausted gases) and the amount of cataclyst, determination of reactor’s size and thermal efficiency (heat emission) of intertubular space
The method of calculation thermochemical conversion of methanol reactor
Keywords: метанол; реактор; газ; конверсия